Beneficial effects of early attention process training after acquired brain injury: A randomized controlled trial - Gabriela Markovic; Marie-Louise Schult; Mattias Elg; Aniko Bartfai (Medical Journals Sweden, 2020)
Background: Evaluation of outcome after intensive cognitive rehabilitation early after brain injury is complicated due to the ongoing biological recovery process. Objective: To evaluate the efficacy of Attention Process Training early after acquired brain injury through time-series measurement with statistical process control. Design: Randomized controlled trial. Method: Patients with acquired brain injury (n = 59) within 4 months' post-injury in interdisciplinary rehabilitation received an additional 20 h of attention training with Attention Process Training or with activity-based attention training. The primary outcome variable was Paced Auditory Serial Attention Test (PASAT) evaluated using statistical process control. Results: Both groups improved (p < 0.001), although a higher number of patients improved with attention process training (χ2 (1, n = 59) = 5.93, p = 0.015) and the variability was significantly decreased. The Attention Process Training group maintained or improved performance at 6 months follow-up (χ2 (1, n = 51) = 6,847, p = 0.033). Attention Process Training required fewer intervention hours for improvement. Based on individual performance, 3 improvement trajectories were identified: stationary, steady, and rapid improvers. Conclusion: The results indicate that attention training is promising early after acquired brain injury and that Attention Process Training boosts functional improvement. Notably, in the present group of relatively homogeneous patients, 3 different trajectories were identified for recovery after acquired brain injury regardless of intervention.